2023
DOI: 10.1039/d3ce00602f
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution–precipitation synthesis and thermal stability of magnesium whitlockite

Abstract: Magnesium whitlockite (Mg-WH, Ca18Mg2(HPO4)2(PO4)12) is a promising candidate for biomedical application in bone regeneration; however, the fabrication of Mg-WH bioceramics by conventional methods is limited. Mg-WH is known to be...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 48 publications
1
10
1
Order By: Relevance
“…The parameter a was calculated as 10.330 Å, while the parameter c was 37.077 Å. These values are slightly lower compared to those previously reported for Mg-WH, 38,39 Zn-WH 22 and Cu-WH. 27 The Rietveld analysis did not indicate the presence of secondary crystalline phases.…”
Section: Resultscontrasting
confidence: 59%
See 4 more Smart Citations
“…The parameter a was calculated as 10.330 Å, while the parameter c was 37.077 Å. These values are slightly lower compared to those previously reported for Mg-WH, 38,39 Zn-WH 22 and Cu-WH. 27 The Rietveld analysis did not indicate the presence of secondary crystalline phases.…”
Section: Resultscontrasting
confidence: 59%
“…Thus, it can be concluded that the synthetic procedure requires at least 3 h. This value is significantly lower compared to those reported for the solvothermal synthesis of Mn-WH 24 or Zn-WH 23 and comparable to the data reported for hydrothermally synthesized Mg-WH. 38,39 On the other hand, previously it was shown that in an aqueous medium, Zn-WH can be formed just in 1 h. 22 The observed time-dependent phase evolution from DCPD to Cu-WH suggests that the transformation via a dissolution–precipitation reaction could occur not directly, but in two steps with an intermediate HA phase. Previously, it was shown by Jang et al 37 that under certain conditions HA can be converted into Mg-WH via a multistep process; however, it is difficult to compare the phase transformations in certain systems due to plenty of influencing factors such as pH, temperature, pressure, chemical composition of the reaction mixture, etc .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations